Constructing Polish Heteroimage in the Interwar Novels of the Wider Ostrava Region: A Comparative Czech-German Study - Pěchula, Lukáš (Porównania, 2020)
This analysis aims to examine the construction of the Polish heteroimages in novels written between two World wars in the broader region Ostravsko. It is a comparative study which reflects Polish ethnotypes in a wide range of Czech and German authors. Broader Moravian-Silesian region was the target of Polish immigration, but especially Ostrava was also a multicultural center where Polish, Czech, German and Jewish People lived side by side. It is these specifics that create space for the interesting development of all ethnotypes which are the basis of this research.